2005
DOI: 10.1097/00001756-200507130-00009
|View full text |Cite
|
Sign up to set email alerts
|

Age-related effects on superior temporal gyrus activity during an auditory oddball task

Abstract: We used magnetoencephalography in combination with magnetic resonance imaging to investigate the effects of aging on the temporal dynamics of activity localized to several brain regions during an auditory oddball task. The most interesting effects were noted in the superior temporal gyrus as follows: (1) responses were generally stronger to rare than to frequent tones throughout the entire 600-ms time interval, and (2) increases in the amplitude of the 40-ms peak and the latency of the maximum late response we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
13
0
Order By: Relevance
“…The age-related increase in P1m amplitude is consistent with prior studies (Kovacevic et al, 2005;Pekkonen et al, 1995;Ross et al, 2009) and may reflect older adults' reduced ability to filter out task-irrelevant information (Alain and Woods, 1999;Chao and Knight, 1997;Gazzaley et al, 2005;West and Alain, 2000), which has been related to a decline in prefrontal inhibition (Alain and Woods, 1999;Chao and Knight, 1997;West, 1996). Empirical support for this proposal includes studies in humans that show increased amplitudes of middle latency auditory evoked responses following lesions to the dorsolateral prefrontal cortex (Alho et al, 1994;Knight et al, 1989).…”
Section: Effect Of Age On Aefsupporting
confidence: 83%
“…The age-related increase in P1m amplitude is consistent with prior studies (Kovacevic et al, 2005;Pekkonen et al, 1995;Ross et al, 2009) and may reflect older adults' reduced ability to filter out task-irrelevant information (Alain and Woods, 1999;Chao and Knight, 1997;Gazzaley et al, 2005;West and Alain, 2000), which has been related to a decline in prefrontal inhibition (Alain and Woods, 1999;Chao and Knight, 1997;West, 1996). Empirical support for this proposal includes studies in humans that show increased amplitudes of middle latency auditory evoked responses following lesions to the dorsolateral prefrontal cortex (Alho et al, 1994;Knight et al, 1989).…”
Section: Effect Of Age On Aefsupporting
confidence: 83%
“…MEG can separate out activity which is primarily sensoryrelated versus activity in sensory or other regions that are modulated by attention or become sustained due to working memory task demands . According to our MEG studies, initial sensory-related activity in auditory and somatosensory cortices (~40 ms and 20 ms, respectively) are enhanced in amplitude for the elderly, not decreased Kovacevic et al, 2005;Stephen et al, 2006). …”
Section: Introductionmentioning
confidence: 61%
“…Several MEG studies have examined the neurophysiological underpinnings of healthy aging using auditory processing paradigms, and have shown that older adults generally demonstrate a stronger amplitude response relative to younger adults in superior temporal regions shortly after the onset of an auditory stimulus (∼50ms). This accentuated early neural response has been demonstrated in response to complex sounds, 138 phonetic sounds, 139-140 spoken words, 141 pitch, 142-143 and tones. 139,144-145 Interestingly, similar age-related differences have been reported in somatosensory MEG studies utilizing median nerve stimulation, with older adults exhibiting an increased early cortical response in the primary somatosensory cortices, 146-151 especially contralateral to the stimulated nerve.…”
Section: Healthy Agingmentioning
confidence: 79%